2019
DOI: 10.2147/ndt.s190725
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinical factors influencing resilience in patients with anorexia nervosa</p>

Abstract: PurposeThis study was to elucidate clinical factors influencing resilience in anorexia nervosa (AN) patients.Patients and methodsTwenty female patients with AN (median age =30.0 years, quartile deviation =6.8) and 40 female healthy controls (HCs) (median age =30.0 years, quartile deviation =8.6) participated in the present study. Resilience was assessed with the Connor– Davidson resilience scale (CD-RISC). Clinical symptoms were evaluated with the structured interview guide for the Hamilton depression rating s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
(31 reference statements)
1
2
0
Order By: Relevance
“…Moreover, resilience may predict the individuals’ ability to improve when presented with adverse life difficulties [ 59 ]. In line with our findings, previous studies have also found lower resilience in patients with AN compared to control participants, associating this finding with the presence of interoceptive confusion, interpersonal difficulties, negative self-image, and ineffectiveness in patients with AN, as well as with an influence of the ED-related pathology per se [ 60 , 61 ].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, resilience may predict the individuals’ ability to improve when presented with adverse life difficulties [ 59 ]. In line with our findings, previous studies have also found lower resilience in patients with AN compared to control participants, associating this finding with the presence of interoceptive confusion, interpersonal difficulties, negative self-image, and ineffectiveness in patients with AN, as well as with an influence of the ED-related pathology per se [ 60 , 61 ].…”
Section: Discussionsupporting
confidence: 92%
“…The common feature of resilience manifests in its dynamic nature, i.e., the ability of a system (e.g., a material, a plant, or a brain) exposed to a harmful stimulus to absorb, accommodate or adapt to the effects of the stress in an efficient manner by adjusting its structure, organization, physiological mechanisms, metabolic regulation, mode of action, etc. The resilience phenomenon is also commonly observed in human neurological diseases, particularly in neurodegenerative and neuropsychiatric diseases 11,[16][17][18][19][20] . Despite exposure to traumatic events or even to the presence of advanced pathophysiological changes, some people do not exhibit behavioral and psychological symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…The literature supports an association between negative self-image, feelings of being rejected by others, and resilience among patients with anorexia nervosa. 3 There is also evidence from a clinical population of adolescents that body size dissatisfaction is a predictor of low resilience. 4 In a qualitative study of adults recovering from EDs, authors suggest a multilevel resilience framework as a potential strategy for treatment and recovery.…”
Section: Introductionmentioning
confidence: 99%